Penguatan Branding dan Pengemasan Produk UMKM di Desa Duren Seribu Kota Depok - Oktaviani, Retno Fuji; Niazi, Hakam Ali; Thoha, Muhammad Nuur Farid; Anwar, Syaiful ; Prasetya, Rizky Eka (Penerbit Goodwood, 2024)
Purpose: This service aims to increase the attractiveness of MSME products in Duren Seribu Village, Depok City, by strengthening branding and packaging. Methodology/Approach: This service was designed using community-based assessment methods. This study included a market review of brand name and logo selection, packaging design, brand promotion, and communication strategies. This review process involved MSME owners, product users, and branching experts. In addition, we used graphic design software and data analysis tools to optimize branching and packaging. Results: The results of this service show that strengthening Branding and packaging can increase the attractiveness of MSME products. Strategies such as choosing a logo and brand name, attractive packaging design, promotion via social media, and creating a brand story have proven effective in strengthening the branching and packaging of MSME products. Limitations: This study provides a transparent assessment of its scope and potential biases. Some limitations may include the small sample size, potential respondent biases, and inherent challenges of capturing the complex and multifaceted nature of the branding and packaging impact on MSMEs. Contribution: This study enriches the literature on UMKM development by providing a nuanced understanding of the role of branding and packaging in rural contexts, specifically within Desa Duren Seribu and Kota Depok. The insights gained from this study may contribute to the formulation of tailored strategies and interventions that can be replicated in similar rural settings, aiding the sustainable growth of the UMKM.